2020
DOI: 10.3390/agronomy10040546
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Metabolic Diversity of Soil Microbiome in Response to Exogenous Organic Matter Amendments

Abstract: Loss of organic matter content of cultivated soils is observed in many regions of Europe. The possibility of using organic waste as a soil additive that enriches the soil with organic matter and essential components is important in soil quality protection and waste management. This research concerned the influence of six organic wastes—two industrial composts, three digestates and meat bone meal—on soil microbial properties. The study of functional microbial diversity concerns the determination of the cataboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 49 publications
3
11
0
Order By: Relevance
“…Our results showed that the MF treatment significantly enhanced the OM content of the soil. Our results are in line with studies published by Gryta et al [33] and Cesarano et al [34] who reported the beneficial effect of OM in replenishing soil microbiome and fertility. Optimum productivity of plants can be ensured only with vital bio-available nutrients in the soil [33,34].…”
Section: Discussionsupporting
confidence: 94%
“…Our results showed that the MF treatment significantly enhanced the OM content of the soil. Our results are in line with studies published by Gryta et al [33] and Cesarano et al [34] who reported the beneficial effect of OM in replenishing soil microbiome and fertility. Optimum productivity of plants can be ensured only with vital bio-available nutrients in the soil [33,34].…”
Section: Discussionsupporting
confidence: 94%
“…At the same time, the enzymes related to organic carbon mineralization, i.e., K05349 (beta-glucosidase [EC: 3.2.1.21]) and K15371 (glutamate dehydrogenase (GDH2) [EC: 1.4.1.2]), decreased. These results showed that the soil management under rainfed conditions proposed in this study (i.e., compost amendment and incorporation of weed biomass in an olive grove) affected some pathways of soil metabolism and environmental information processing in a manner comparable to that evidenced by other authors and for conservation management [54,55], promoting the humification of both exogenous and natural organic carbon [56]. Finally, we did not find significant differences in the global metabolic pathways related to the P cycle (K01113_K01077_alkaline phosphatase).…”
Section: Bacterial Community Functional Potentialsupporting
confidence: 77%
“…Different fertilization methods, both organic and inorganic, are known to influence the activity and biodiversity of soil microorganisms. The introduction of various substances to the soil may change the composition of indigenous microbiota and modify processes taking place in the soil environment [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The CLPP analysis using BIOLOG plates was prepared in the following way: 1 g of fresh soil was suspended in 99 mL of sterile saline peptone water and shaken for 20 min at 20 • C before being incubated for 30 min at 4 • C. Afterwards, each well of the BIOLOG ECO plate and FF plate was inoculated with a prepared suspension of 120 µL and 100 µL respectively, and incubated at 23 • C. Absorbance readings were performed at 590 nm in the case of ECO plates and at 750 nm as for FF plates with a BIOLOG MicroStation plate reader (Biolog ® , Hayward, CA, USA) every 24 h for 216 incubation hours. Detailed procedures of the analyses were described by Wolińska et al [135] and Gryta et al [35].…”
Section: Community Level Physiological Profiling (Clpp)mentioning
confidence: 99%